Changes in birth outcomes and utilization of prenatal care during the COVID-19 pandemic in 2020: a secondary analysis of vital statistics in Colombia - Carol C. Guarnizo-Herreño; Giancarlo Buitrago; George L Wehby (BMC, 2023)
Abstract Background Birth outcomes could have been affected by the COVID-19 pandemic through changes in access to prenatal services and other pathways. The aim of this study was to examine the effects of the COVID-19 pandemic on fetal death, birth weight, gestational age, number of prenatal visits, and caesarean delivery in 2020 in Colombia. Methods We conducted a secondary analysis of data on 3,140,010 pregnancies and 2,993,534 live births from population-based birth certificate and fetal death certificate records in Colombia between 2016 and 2020. Outcomes were compared separately for each month during 2020 with the same month in 2019 and pre-pandemic trends were examined in regression models controlling for maternal age, educational level, marital status, type of health insurance, place of residence (urban/rural), municipality of birth, and the number of pregnancies the mother has had before last pregnancy. Results We found some evidence for a decline in miscarriage risk in some months after the pandemic start, while there was an apparent lagging increase in stillbirth risk, although not statistically significant after correction for multiple comparisons. Birth weight increased during the onset of the pandemic, a change that does not appear to be driven by pre-pandemic trends. Specifically, mean birth weight was higher in 2020 than 2019 for births in April through December by about 12 to 21 g (p < 0.01). There was also a lower risk of gestational age at/below 37 weeks in 2020 for two months following the pandemic (April, June), but a higher risk in October. Finally, there was a decline in prenatal visits in 2020 especially in June-October, but no evidence of a change in C-section delivery. Conclusions The study findings suggest mixed early effects of the pandemic on perinatal outcomes and prenatal care utilization in Colombia. While there was a significant decline in prenatal visits, other factors may have had counter effects on perinatal health including an increase in birth weight on average.